Work education in grade four in three districts in the Division of Rizal - Cruz, Amado C. 1946- (s.n.], 1969)
The study presents a mass of information and data on the status of the teaching of work education in Grade IV in three districts in the Division of Rizal. The main purpose of the study is to furnish the school officials' knowledge of facts that can serve as bases for formulating school policies and guidelines in the area.